Joyce J. Scott Harriet Tubman and other truths - Sims, Patterson; Rodney, Seph (Grounds for Sculpture, 2018)
The most comprehensive publication available to date on the work of Baltimore-based, African American artist Joyce J. Scott (born 1948), this beautiful monograph features more than 60 works from the last 45 years, including 12 new pieces based upon Harriet Tubman. Exploring subjects of representation, politics and topical events involving African Americans and oppressed people worldwide, 'Joyce J. Scott: Harriet Tubman and Other Truths' showcases the beauty of Scott's art, mastery of her materials and provocative worldviews. Essays by co-curators Lowery Stokes Sims and Patterson Sims, an interview with the artist and commentary by Seph Rodney provide rich narrative and context. Exhibition: Grounds for Sculpture, Hamilton, USA (20.10.2017-01.04.2018)
Catalog of an exhibition held at Grounds for Sculpture, Hamilton, New Jersey, October 20, 2017-April 1, 2018
Includes an interview with the artist, conducted by Lowery Stokes Sims
Keywords: Scott, Joyce -- 1948-; Plastik; Scott, Joyce / 1948- / Exhibitions; Ausstellungskatalog -- Grounds for Sculpture -- 20.10.2017-01.04.2018 -- Hamilton, New Jersey; Bildband